A rigid-axle-based molecular rotaxane channel facilitates K+/Cl− co-transport across a lipid membrane. Issue 26 (10th March 2023) - Pang, Shihao; Sun, Xiaonan; Yan, Zexin; Wang, Chuantao; Ye, Kai; Ma, Shinan; Zhu, Linyong; Bao, Chunyan
Abstract : A rigid-axle-based molecular rotaxane was designed to mediate efficient K + /Cl − channel co-transport by simultaneously introducing heteroditopic receptors, which presents a new model for designing synthetic channels for salt co-transport. Abstract : Inspired by the design criteria of heteroditopic receptors for ion-pair binding, we herein describe a new strategy to construct a rotaxane transporter (RR[2] ) for K + /Cl − co-transport. The use of a rigid axle improves the transport activity with an EC50 value of 0.58 μM, presenting a significant step toward developing rotaxane artificial channels.